CULTURAL SIGNIFICANCE OF THE PLAY ‘BAWA JITTO’: A DISCOURSE ANALYSIS APPROACH - Sheeba Hassan; Shahnawaz Bhat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The legend of Bawa Jitto is a significant part of Jammu’s folklore, portraying the sacrifice of a pious farmer who stood against injustice. More than a folk hero, Bawa Jitto is revered as a deity in the region, with narratives surrounding him serving as a medium for cultural expression and preservation. This study employs a discourse analysis framework to examine the linguistic, stylistic, and socio-cultural dimensions of the Bawa Jitto narrative, uncovering how meaning is constructed. Through an in-depth analysis of characters, plot structure, setting, dialogue, symbols, and themes, the research explores identity strategies, narrative techniques, and recurring motifs to reveal the play’s moral, social, cultural, and historical significance. Using Professor Ramnath Shastri’s Dogri play Bawa Jitto as the primary source, this study highlights the richness and uniqueness of Dogri cultural norms and values, while also examining the complex interplay between language, culture, and power in shaping social meaning.